Identificação do perfil plasmático e diferenciação das frações de proteínas plasmáticas em ratitas - Battisti, Luciano de Oliveira (2009)
The introduction of new species within the cattle sector has been growing and among the most representative animals in this sector is the ostrich (Struthio camellus). Although generating benefits, these activities are difficult to be deeply studied in terms of their physiology, pathology and clinics due to the speed they evolve. Many physiological parameters which are essential for the diagnosis of disturb and diseases are not available. Thus, the objective of this work was to outline the plasmatic protein electrophoresis profile of ostrich, as well as to identify differences among the fractions of these proteins among specific age groups. Blood samples of 72 ostriches were collected in different farms in Rio Grande do Sul. The samples were distributed in six groups, according to the animal s age and gender, in which 2 were chick, 2 young and 2 adults. These samples were submitted to the biuret method and to the electrophoresis, for quantification, separation and identification of proteins. Along the same line of study, there were also processed and analyzed 9 blood samples of adult rheas (Rhea americana) and a couple of emus (Dromaius novaehollandiae), these animals that, along with the ostrich, which also belong to the Struthioniformes order. The levels of Total Proteins (PPT) and the relation between Albumin and Globulin (A/G) were found and determined through the biuret method and the technique of electrophoresis. For each group of female ostrich chick, the average PPT was 2.23 ± 0.23g/dL, for male chick it was 2.40 ± 0.30g/dL, for young females the average was 3.67 ± 0.42g/dL and young males it was 3.90 ± 0.44g/dL; the adult females presented an average of 4.11 ± 0.65g/dL and the adult males, 4.07 ± 0.69g/dL. For the group of adult rheas were found average values of 5:22 ± 0.66 g / dL of total plasma proteins and 0.97 ± 0.24 for the relationship between albumin and globulins. For a couple of emus, in turn, resulted in values of 5.30 g / dL and 4.10 g / dL of plasma total protein and 0.67 and 0.81 for the ratio of albumin and globulin, for female and male respectively. The protein fractions were defined as albumin, alpha-globulin, beta 1-globulin, beta2-globulin e gamma-globulin for the three species.